Síndrome da Ardência Bucal: terapia com estimulação salivar mecânica, qualidade de vida e transtornos psiquiátricos - Fabrício Tinoco Alvim de Souza (2011)
Introduction: Burning mouth syndrome (BMS) is a chronic disorder characterized by symptoms of oral constant burning with aspect of the mucosa appears normal and no clinical laboratory findings that can diagnose other diseases. Multiple factors have been associated with the development of this disease, including changes in salivary and psychiatric disorders. This condition can affect quality of life of affected individuals. Objective: To evaluate the effects of salivary stimulation therapy on the salivary flow, quality of saliva and symptoms in patients with BMS; assess the quality of life and psychiatric disorders in individuals with BMS. Materials and Methods: Twenty-six BMS patients underwent treatment with salivary mechanical stimulation, using mechanical sialogogue. Resting and stimulated saliva were collected before, during and after 90 days of therapy. Salivary levels of total protein, brain-derived neurotrophic factor (BDNF), interleukin-10 (IL-10), tumor necrosis factor- (TNF-), IL-6 and nerve growth factor (NGF) were assessed before and 90 days after therapy by ELISA. A clinical evaluation of symptoms of SAB was performed 6 months after initiation of therapy. Twenty-six BMS patients and twenty-seven subjects controls were matched by sex and age and interviewed by the SF-36 and OHIP-49. For psychiatric groups counted thirty individuals with SAB and thirty-one control subjects. Both groups were interviewed using the MINI-Plus for psychiatric diagnoses and then applied the following psychometric scales: Rating Scale Hamilton Depression, Beck Depression Inventory, Inventory trait anxiety state (STAI), Epworth Sleepiness Scale, Dutch Fatigue Scale (DUFS) Dutch Exertion Fatigue Scale (DEFS). The intensity of symptoms was measured using two scales: verbal descriptor scale (VDS) and visual analog scale (VAS). Results: A significant reduction in burning sensation and number of sites for burning was verified by the used pain scales (VDS and VAS), as well as an improvement of taste disturbances and xerostomia were observed after therapy. The salivary flow was not significantly modified. However, the therapy resulted in a significant decrease in levels of salivary protein and an increase in TNF-. The scores of the SF-36 and OHIP-49 were significantly worse in all domains than control subjects (P 0.05). The analysis showed that individuals with psychiatric SAB have more pictures of current and past major depressive disorder, generalized anxiety disorder, hypochondriasis, cancer phobia, and that may be associated with morbid (P 0.05). In questionnaires given to subjects had worse scores on Hamilton Rating Scale Depression, Beck Depression Inventory, STAI and DUFS (P0.05). Conclusions: Patients with BMS who used treatment with salivary mechanical stimulation had a reduction of clinical symptoms. The BMS has a negative impact on quality of life of patients. Patients with BMS have a higher presence of psychiatric disorders.